2023
DOI: 10.7759/cureus.35624
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study and Branching Patterns of External Carotid Artery Using Computed Tomography Angiography Among the South Indian Population: A Retrospective Study

Abstract: Introduction:The prime source of vascularization to the head and neck region is through the carotid arteries. The terminal branches of common carotid arteries, such as external carotid artery (ECA) and internal carotid artery (ICA), and their branches are crucial due to the wide area of distribution and variations in their branching pattern. The branching pattern and morphometry are essential for surgeons in the planning and execution of head and neck surgeries. Therefore, this study was conducted to observe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…The incidence of the LFT was variably reported, the unilateral cases being or not being distinguished from the bilateral ones (Table 1). Of these studies, a computed tomography study on 100 cases found a 15% prevalence of LFTs [28]. A different angioCT study on 76 cases found a prevalence of the LFT of 15.5%, but the uni-and bilateral cases were not distinguished [29].…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of the LFT was variably reported, the unilateral cases being or not being distinguished from the bilateral ones (Table 1). Of these studies, a computed tomography study on 100 cases found a 15% prevalence of LFTs [28]. A different angioCT study on 76 cases found a prevalence of the LFT of 15.5%, but the uni-and bilateral cases were not distinguished [29].…”
Section: Discussionmentioning
confidence: 98%